Optimalisasi Konten Libmodo untuk Membangun Research Library - Nurhalisma, Lisna; Suhardini, Dini; Anggini Saktiani, Isma; Syafitri, Nanda Khaerunnisa (Literatify: Trends in Library Developments, 2025)
Academic library have a significant role in realizing the Tri Dharma of Higher Education, especially in the fields of education and research. As a center of information resources, competent librarians are needed, especially in writing scientific papers, which are one of the results of education and training activities. The actions is needed to support the development of science and library services as a research library. However, the interest in writing scientific papers among librarians is still very low, so they must be motivated to produce scientific papers, one of which is through the Libmodo platform. This study aims to determine how to optimize the Libmodo training platform to improve librarians' scientific writing competencies. Using a quantitative approach with descriptive methods and pre-experimental design, data were collected through questionnaires distributed to librarians. The results showed a significant increase in librarian knowledge after participating in the training, which was measured through pretests and posttests. This increase indicates that independent learning using modules on the Libmodo platform is efficacious in improving librarians' scientific writing knowledge and skills.